Impact of diet on attention-deficit hyperactivity disorder in a tertiary care hospital of Rawalpindi - Khan, Tayyab Mumtaz; Akram, Jehanzeb; Zamir, Zarish; Rafay, Abdul; Saher, Sania; Khalid, Rudabah; Munir, Muhammad Arslan; Mehmood, Atif; Tariq, Rida; Khan, Shahrukh (International Journal Of Community Medicine And Public Health, 2023)
Background: Attention-deficit hyperactivity disorder (ADHD) is a prevalent neuropsychiatric disorder of children that affects almost all aspects of the life. The role of diet in the management of the ADHD is understudied in Pakistan. This study aimed to assess the impact of different types of diet on the symptoms of ADHD among the children with ADHD. Methods: This descriptive cross-sectional study was conducted among 58 children with ADHD in Rawalpindi. Ethical approval and informed consent were obtained. Patients’ recruitment was done via developed criteria and Convenient sampling technique. Descriptive statistics and one-way ANOVA were used to determine the difference of ADHD severity among various frequencies of different included foods via Conner Parent rating scale-revised short form. Data analysis was performed by SPSS version 25.0. Results: The difference in hyperactivity index, impulsivity, and learning problems score on CPR-RS among various frequencies of carbohydrate, protein rich and fat foods, was statistically significant and with the increase intake of carbohydrate and protein rich foods, the score on CPR-RS of hyperactivity index, impulsivity, and learning problems also goes up. Whereas, with the increase intake of fat rich foods, the score of hyperactivity index, impulsivity, and learning problems goes down. Conclusions: In short, the high intake of carbohydrate and protein rich foods, increase the severity of the symptoms of ADHD, while, high intake of fat rich foods decreases the severity of the symptoms of ADHD among children.